2005
DOI: 10.1038/nm1186
|View full text |Cite
|
Sign up to set email alerts
|

The breast cancer resistance protein BCRP (ABCG2) concentrates drugs and carcinogenic xenotoxins into milk

Abstract: Contamination of milk with drugs, pesticides and other xenotoxins can pose a major health risk to breast-fed infants and dairy consumers. Here we show that the multidrug transporter BCRP (encoded by ABCG2) is strongly induced in the mammary gland of mice, cows and humans during lactation and that it is responsible for the active secretion of clinically and toxicologically important substrates such as the dietary carcinogen PhIP, the anticancer drug topotecan and the antiulcerative cimetidine into mouse milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
295
3
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 378 publications
(315 citation statements)
references
References 11 publications
15
295
3
2
Order By: Relevance
“…However, there is some controversy over how universal this association may be [29,30]. Recently, we have demonstrated that Bcrp1 is highly expressed in the apical membrane of mammary alveolar epithelial cells during late pregnancy and lactation, whereas it is not detectable in mammary epithelial cells of virgins [31]. Here we show that in virgin mice, a small number of cells in mammary ducts were found to express Bcrp1.…”
Section: Discussionmentioning
confidence: 57%
“…However, there is some controversy over how universal this association may be [29,30]. Recently, we have demonstrated that Bcrp1 is highly expressed in the apical membrane of mammary alveolar epithelial cells during late pregnancy and lactation, whereas it is not detectable in mammary epithelial cells of virgins [31]. Here we show that in virgin mice, a small number of cells in mammary ducts were found to express Bcrp1.…”
Section: Discussionmentioning
confidence: 57%
“…In an ATPdependent process, ABCG2 transports various xenobiotics and cytostatic drugs across the plasma membrane (Litman et al 2000). Analysis of different stages of mammary development by immunohistochemistry and Western analysis revealed that ABCG2 was not expressed in virgin mice but was greatly induced during late pregnancy and especially during lactation (Jonker et al 2005). They demonstrated that ABCG2 expression is confined to the apical membrane of alveolar, but not ductal mammary epithelial cells of mice, cows, and humans and is responsible for the active secretion of clinically and toxicologically important substrates into mouse milk.…”
Section: Discussionmentioning
confidence: 99%
“…A single nucleotide polymorphism (SNP) capable of encoding a substitution of tyrosine-581 to serine in ABCG2 is most likely responsible for the major QTL affecting milk yield and composition. Jonker et al (2005) demonstrated that ABGC2 is responsible for the active secretion of clinically and toxicologically important substrates into mouse milk, and that mice homozygous for By combining comparative genomics and in silico gene cloning, we produced a map of genes and sequence variation in the critical region of the QTL (Fig. 1).…”
mentioning
confidence: 99%
“…The results of biodistribution and functional studies have indicated that BCRP plays important physiologic and pharmacologic roles, particularly in the clearance of toxic agents from the gastrointestinal tract, blood-brain barrier, liver, placenta, and mammary glands (22,38,39). With respect to hematologic cells, BCRP has been identified in hematopoietic stem cells (40) and dendritic cells (41).…”
mentioning
confidence: 99%